2021
DOI: 10.3390/nu13114052
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Starch Consumption Effects on Glycemic Control and Glycemic Variability in Patients with Type 2 Diabetes: A Randomized Crossover Study

Abstract: We previously observed beneficial effects of native banana starch (NBS) with a high resistant starch (RS) content on glycemic response in lean and obese participants. Here, we aimed to determine the effects of NBS and high-amylose maize starch (HMS) on glycemic control (GC) and glycemic variability (GV) in patients with type 2 diabetes (T2D) when treatments were matched for digestible starch content. In a randomized, crossover study, continuous glucose monitoring (CGM) was performed in 17 participants (aged 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…Of the studies which could not be included in the meta-analysis, three reported that the addition of resistant starch to the diet did not affect fasting glucose or insulin ( 36 , 39 , 40 ). One study ( 38 ), reported that resistant starch type 2 lowered fasting glucose but did not affect fasting insulin. Conversely, Ble-Castillo et al ( 37 ), reported that resistant starch type 2 significantly reduced fasting insulin but did not affect fasting glucose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies which could not be included in the meta-analysis, three reported that the addition of resistant starch to the diet did not affect fasting glucose or insulin ( 36 , 39 , 40 ). One study ( 38 ), reported that resistant starch type 2 lowered fasting glucose but did not affect fasting insulin. Conversely, Ble-Castillo et al ( 37 ), reported that resistant starch type 2 significantly reduced fasting insulin but did not affect fasting glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported that the addition of resistant starch 2 to the diet, had no significant effect on HOMA-IR ( 36 , 38 ) or HOMA-%B and -%S ( 36 ). However, Ble-Castillo et al ( 37 ) reported an increase in HOMA-IR after resistant starch supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Arias-Córdova et al [ 36 ], it was found that the native banana starch (NBS) with a content of 70.5% resistant starch and 10% digestible starch caused a reduction in fasting blood glucose from baseline compared with digestible maize starch with 100% digestible starch content. There was improvement in insulin sensitivity and significant improvement in glycaemic control including significant reduction in parameters such as HbA1c, postprandial blood glucose and fasting blood glucose levels in patients with type 2 diabetes who consumed prebiotic diets compared with control in some studies [ 31 , 38 , 41 , 43 , 44 , 48 ].…”
Section: Glycaemic Controlmentioning
confidence: 99%
“… Graphs showing ( a ) risk of bias ( b ) risk of bias summary [ 18 , 31 , 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation